Simulated climatology and evolution of aridity in the 21st century. Issue 12 (25th June 2015) - Lin, Lei; Gettelman, Andrew; Feng, Song; Fu, Qiang
Abstract Future changes in aridity, defined as the ratio of annual precipitation to potential evapotranspiration (PET), are analyzed using simulations from the Community Earth System Model (CESM) Large Ensemble (LE) and the phase 5 of the Coupled Model Intercomparison Project (CMIP5) during the period 1980–2080. Both CESM and CMIP5 ensembles can reproduce the observed temporal and spatial variability of aridity. On the interannual time scale, annual average PET is sensitive to the variability of relative humidity, net surface energy flux, and surface air temperature, while the precipitation variability is the dominant component of annual average aridity sensitivity. For the long‐term trends, differences between the two ensembles illustrate that the impact of the internal variability is smaller than that of the model structural uncertainty with the trends from the CMIP5 ensemble of models having a much larger spread than those from the single‐model CESM‐LE. The annual mean aridity averaged over global land increases (becomes drier) by 6.4% in 2055–2080 relative to 1980–2005. Aridity trends differ by region in the ensemble mean. In the future, increasing precipitation leads to decreasing aridity over northwest China and central (or tropical) Africa, while decreasing precipitation leads to drying (increasing aridity) in the subtropics, northern and southern Africa, and the Amazon. Increases in PET can lead to increasing aridity even in regions with increasing precipitation.